Perancangan Sistem Donasi Kepada Penulis Ilmiah Dengan Blockchain Ethereum Berbasis Ekstensi Browser - Laurenso, Justin; Yohannis, Alfa Ryano (The Indonesian Journal of Computer Science, 2024)
This research highlights the challenges faced by scientific authors, especially regarding the lack of recognition, financial support, and appreciation. An innovative solution is proposed through the application of blockchain technology, specifically Ethereum, to improve transparency and security in the donation flow. Using such an approach, this research aims to provide a solution to the problem as well as open up wider collaboration opportunities within the research community. This research involves steps such as literature study, system analysis, system development, and report generation. In system development, the SDLC (Software Development Life Cycle) methodology with a structured waterfall model is used and is suitable for designing a donation system with blockchain technology. This research successfully developed a donation system integrated with the ethereum blockchain based on browser extensions. The unit testing results show that the functions used run well. It is hoped that this research can make a significant contribution in supporting scientific writers, strengthening transparency in the flow of donations, and becoming a foundation for further research in this field.